The Impact of Consumer Interests, Security Risks, and Financial Behavior on New Transaction Tool (E-Money). - Medilla Laila; Mahlia Muis; Dian A.S. Parawansa (Magister Management, Hasanuddin University, 2020)
This study aimed to analyze the impact of interests, security risks, and financial behavior on new tools in transactions (e-money). Five direct relationships have been built resulting in two equations. To evaluate the model, the study distributed questionnaires to 110 respondents from seven different companies. With the use of path analysis, the model is then tested. On the basis of the statistical results, the findings show that consumer interest and safety risk have a positive and significant impact on financial behavior. To the relationship to electronic money, customer interest and financial behavior indicate a positive and significant relationship. Interestingly, customer safety risk did not show an insignificant result.